UNDERSTANDING PREMARITAL SEXUAL ATTITUDE AND BEHAVIOR: THEORITICAL AND EMPIRICAL CONTEXTS - - Faturochman (Buletin Psikologi, 2003)
Sexual activity among teenage populations has tended to increase as indicated by a decrease in the age at the first intercourse and the increasing proportion of sexually active teenagers (Forrest and Singh, 1990; Hofferth et al., 1987). Sexually active adolescents are faced by pregnancy and sexually transmitted disease problems because they are usually not protected. They do not know enough about the consequences of their sexual activities nor are they often aware of the range of contraceptive methods available as a means of protection. Alternatively, they may know that there are a lot of contraceptive methods but they do not have access because of societal control. Thelack of accessibility seems to influence the knowledge of the contraception use.